Glucocorticoid receptor ChIP‐sequencing of subcutaneous fat reveals modulation of inflammatory pathways. (26th September 2015) - Singh, Puneet; Brock, Clifton O.; Volden, Paul A.; Hernandez, Kyle; Skor, Maxwell; Kocherginsky, Masha; Park, Julie E.; Brady, Matthew J.; Conzen, Suzanne D.
Abstract : Objective: To identify glucocorticoid receptor (GR)‐associated chromatin sequences and target genes in primary human abdominal subcutaneous fat. Methods: GR chromatin immunoprecipitation (ChIP)‐sequencing (seq) methodology in subcutaneous human adipocytes treated ex vivo with dexamethasone (dex) was optimized to identify genome‐wide dex‐dependent GR‐binding regions (GBRs). Gene expression analyses were performed in parallel ± dex treatment. Results: Fat was obtained from four female surgical patients without obesity with a median age of 50.5 years. ChIP‐seq analysis revealed 219 dex‐associated GBRs. Of these, 136 GBRs were located within 100 kb of the transcriptional start site and associated with 123 genes. Combining these data with dex‐induced gene expression, 70 of the 123 putative direct target genes were significantly up‐ or downregulated following 4 hours of dex treatment. Gene expression analysis demonstrated that the top 10 pathways reflected regulation of cellular metabolism and inflammation. DEPTOR, an inhibitor of mTOR, was identified as a potential direct GR target gene. Conclusions: This is the first report of genome‐wide GR ChIP‐seq and gene expression analysis in human fat. The results implicate regulation of key GR target genes that are involved in dampening inflammation and promoting cellular metabolism.